Business law and its effects on commercial transactions - Isretno Israhadi, Evita (Opción, 2019)
This study surveyed the Indonesian business law, import andjoint venture licensing regulations and found out how the law hasimplemented sweeping regulations imposing non-automatic importlicensing procedures. The study adopted a qualitative method approachemploying the inductive method of collecting data. As a result, theIndonesian business law even violated the WTO agreement byintroducing arbitrary regulations sanctioning imports in a few cases. Inconclusion, the government must also try to accelerate regulatoryreforms, particularly in services sectors where market restrictions havebeen shown to negatively affect trade in manufactured goods.